Subtypes of gestational diabetes and future risk of pre-diabetes or diabetes. (October 2021) - Retnakaran, Ravi; Ye, Chang; Hanley, Anthony J.; Connelly, Philip W.; Sermer, Mathew; Zinman, Bernard
Abstract: Background: Recent studies have suggested that gestational diabetes (GDM) is a heterogeneous condition with distinct subtypes determined by whether the predominant metabolic abnormality is impaired insulin sensitivity or deficient insulin secretion. However, it is not known if the elevated future risk of pre-diabetes/diabetes associated with GDM varies according to these subtypes. Thus, we sought to evaluate maternal metabolic function in the 1st year postpartum in relation to GDM subtypes. Methods: In this prospective cohort study conducted in Toronto, Canada, 613 women underwent GDM screening by oral glucose tolerance test (OGTT) in pregnancy, followed by repeat OGTT at both 3-months and 12-months postpartum between 09/2003 and 03/2016. The antepartum OGTT identified 3 groups of women: GDM with predominant sensitivity defect (GDM-sensitivity), GDM with predominant secretion defect (GDM-secretion), and non-GDM. Findings: Antepartum findings persisted after pregnancy, with lower insulin sensitivity in GDM-sensitivity (Matsuda index; HOMA-IR) and lower insulin secretion in GDM-secretion (Stumvoll first-phase; insulinogenic index (IGI)) at both 3-months and 12-months (all p <0.005). Beta-cell compensation (Insulin Secretion-Sensitivity Index-2; IGI/HOMA-IR) was lower in both GDM subtypes compared to non-GDM (all p <0.0005) but did not differ between GDM-sensitivity and GDM-secretion. Similarly, both subtypes exhibited higher post-challenge glycemia on OGTT at 3-months and 12-months than non-GDM (all p <0.0005) but did not differ from one another. The prevalence of pre-diabetes/diabetes was higher in both GDM-sensitivity (30.9%; 95%CI: 21.7–41.2) and GDM-secretion (27.6%; 16.7–40.9) than in non-GDM (10.4%; 7.7–13.6) at 12-months (both p <0.005), with no difference between GDM subtypes ( p = 0.75). Interpretation: Beta-cell dysfunction, glycemia and incident pre-diabetes/diabetes do not vary between GDM subtypes in the 1st year postpartum. Funding: Canadian Institutes of Health Research; Diabetes Canada